Silicone Surface Modification with Collagen and Its Biological Responses - Liu, Lihua (My University, 2006)
Collagen, due to its good biocompatibility and abundance in mammalian structures, has been widely applied in developing better biomaterials. There remains the need for yet more stable surfaces of biomaterials. One strategy to achieve this is improved binding to surfaces using covalent rather than physical linking. However, due to collagen's poor solubility in neutral or alkaline conditions, there are only a few papers describing covalently linked collagen so far, and they generally use acidic conditions to generate surfaces with only low collagen density. N-Hydroxysuccimide ester (NHS) chemistry has been widely used in covalently binding proteins, but the NHS activity and its preparation efficiency are plagued with undesired, premature hydrolysis. A two-step method was developed for making NHS functional surfaces with a non-fouling spacer, PEO. The process was more efficient and led to concentrated NHS surfaces. Collagen was successfully immobilized onto this NHS surface after optimizing the conditions for immobilization. The solubility problem was overcome by increasing the ionic strength of the solution. Abundant collagen molecules could then be immobilized on the silicone surface. ATR-FTIR was used as a diagnostic tool to prove the surface had been modified. The low water contact angle (40°) indicated the presence of collagen. XPS data showed a significant increase on the nitrogen content after tethering collagen molecules. Deep freezing ToF-SIMS displayed a decrease in the peak intensity for cationic fractions of collagen molecules when warming from -96 °C to room temperature, which suggested the surface rearrangement due to the hydrophilic character of collagen. Profilometer and tapping-mode AFM were used to investigate the surface morphology after modification. The latter showed a high density mesh work (immobilized collagen fibers) on the collagen-modified surface. Collagen stain with Sirius Red F3B allowed us to look into the tertiary structures of covalently tethered collagen on the surface. However, it was found that only some of them were still in their native form. Interestingly, a subsequent epithelial cell culture assay showed that the cells grew very well on this collagen rich silicone surface. This suggested collagen's tertiary structure may not be necessary to support cell growth on the silicone surface covalently modified with collagen through the PEO spacer. However, further biochemical experiments are required to establish the underlying source of this observation.
Keywords: silicone surface modification, collagen, biological responses, biocompactibility, covalent, proteins, tertiary structures